An alternative perspective on triage systems: the Progressive Real-world Optimization of Triage System (PROGRESS) study - Arian Zaboli; Francesco Brigo; Serena Sibilio; Gloria Brigiari; Magdalena Massar; Norbert Pfeifer; Marta Parodi; Eleonora Rella; Gianni Turcato (Emergency Care Journal)
Triage systems have remained largely unchanged since the 1990s and rely on expert consensus, with no single system consistently outperforming others in accurately identifying critically ill or urgent patients. This study aimed to determine whether incorporating additional tools improves the predictive accuracy of the Manchester Triage System (MTS). A prospective, monocentric study was conducted at Merano Hospital (Italy) from June 1st to December 31st, 2023. A triage nurse and two ED physicians assigned patient priorities. The cohort was split for model derivation and validation. An ordinal logistic regression model was developed using MTS, the National Early Warning Score, and the Charlson Comorbidity Index, then tested on a validation cohort, bootstrapped to 5000 cases. Of the 1270 patients enrolled, 821 were in the derivation cohort and 449 in the validation cohort. The model outperformed MTS alone in most outcomes, except for predicting death at 72 hours and 7 days. Decision Curve Analysis confirmed its superiority in identifying urgent cases. Integrating multiple tools into triage models can enhance their performance, improving patient prioritization accuracy.